2019
DOI: 10.1101/763532
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Gene flow and species delimitation in fishes of Western North America: Flannelmouth (Catostomus latipinnis) and Bluehead sucker (C. Pantosteus discobolus)

Abstract: 2The delimitation of species-boundaries, particularly those obscured by reticulation, is a critical step in contemporary biodiversity assessment. It is especially relevant for conservation and 4 management of indigenous fishes in western North America, represented herein by two species with dissimilar life-histories co-distributed in the highly modified Colorado River (i.e., 6Flannelmouth Sucker, Catostomus latipinnis; Bluehead Sucker, C. Pantosteus discobolus). To quantify phylogenomic patterns and examine pr… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 83 publications
0
6
0
Order By: Relevance
“…In addition, some studies revealed that variation of morphological traits could be caused by ecological factors (Michel, Chien, Beachum, Bennett, & Knouft, 2017; Shuai, Yu, Lek, & Li, 2018). And genealogical break as a key ecological factor which can bring about morphological differences by impeding gene flow between species (Bangs, Douglas, Chafin, & Douglas, 2019). By analysing the geographical distribution of the four species, we observed that native ranges of M. amblycephala , M. skolkovii and M. pellegrini are at the same latitude (30 degrees north), while that of M. hoffmanni is near 24 degrees north latitude, far from the other three species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, some studies revealed that variation of morphological traits could be caused by ecological factors (Michel, Chien, Beachum, Bennett, & Knouft, 2017; Shuai, Yu, Lek, & Li, 2018). And genealogical break as a key ecological factor which can bring about morphological differences by impeding gene flow between species (Bangs, Douglas, Chafin, & Douglas, 2019). By analysing the geographical distribution of the four species, we observed that native ranges of M. amblycephala , M. skolkovii and M. pellegrini are at the same latitude (30 degrees north), while that of M. hoffmanni is near 24 degrees north latitude, far from the other three species.…”
Section: Discussionmentioning
confidence: 99%
“…that variation of morphological traits could be caused by ecological factors (Michel, Chien, Beachum, Bennett, & Knouft, 2017;Shuai, Yu, Lek, & Li, 2018). And genealogical break as a key ecological factor which can bring about morphological differences by impeding gene flow between species (Bangs, Douglas, Chafin, & Douglas, 2019).…”
Section: Ta B L E 4 (Continued)mentioning
confidence: 99%
“…This includes fish species complexes in sticklebacks (Guo et al ., 2019), roaches (Baumsteiger et al ., 2017), cichlids ( e.g . Willis, 2017), suckers (Bangs et al ., 2020), topminnows (Duvernell et al ., 2019) and coregonids ( Coregonus ardeti species flock; Ackiss et al ., 2020). Based on several thousand polymorphisms, Copus et al .…”
Section: The Futurementioning
confidence: 99%
“…oconnori). In addition to gene flow obscuring species boundaries [80,106], parallels drawn between Himalayan streams and another region characterized by extreme freshwater habitats (e.g., the American Southwest [106][107][108]) suggest that the potential for anthropogenically mediated hybridization should not be ignored. Here, 'extinction vortices' may be driven by a coupling of potentially maladaptive hybridization and declining population sizes.…”
Section: (B) Varying Rates Of Hybridization Among Drainagesmentioning
confidence: 99%